Effect of Modification of Deck Properties on Suspension Bridges - Shrestha, Jagat Kumar (Journal of the Institute of Engineering, 2017)
Different type of deck configuration has been used for suspension bridge depending upon different design requirements. Changes in deck properties lead to changes in behavior of a suspension bridge. In this study, effect of deck modification of a existing bridge from timber to steel deck is considered. Three dimensional finite element models is developed and analyzed changing the deck material from timber to steel which causes reduction in weight and changes in design parameters. This changes the dynamic behavior of the bridge and affects the performance of bearings. The study has been carried out in real world problem encountered in Mugling Suspension Bridge over Trishuli River in Nepal. The study has come up with conclusions and recommendations to increase mass of deck material and replacement of bearings for better performance. Journal of the Institute of Engineering, 2016, 12(1): 39-50